Postlecture Evaluation of a Positive Youth Development Subject for University Students in Hong Kong - Daniel T. L. Shek (The Scientific World Journal)
The purpose of this study was to examine the postlecture evaluation by the students taking a course (Tomorrow's Leaders) that attempted to promote their leadership qualities and intrapersonal competencies at The Hong Kong Polytechnic University in Hong Kong. Except for the last lecture, students were invited to respond to a 12-item postlecture questionnaire after each lecture. Results showed that the students had positive perceptions of the subject, class, and teacher attributes, and they had positive global evaluation of the teacher and the subject. The postlecture evaluation questionnaire was found to possess good psychometric properties. Multiple regression analyses showed that subject, class, and teacher attributes were predictive of global evaluation of the lecture and the teacher. In conjunction with other evaluation findings, the present findings strongly suggest that students had positive perceptions of the attributes and benefits of “Tomorrow's Leaders.”